Climatological conditions of the southern Santa Catarina state highlands for hop production - Fagherazzi, Mariana Mendes; Sarnighausen, Valéria Rodrigues [UNESP]; Rufato, Leo; Nerbass, Francine Regianini; dos Santos, Marllon Fernando Soares (FapUNIFESP (SciELO), 2023)
This study aimed to characterize solar brightness, photoperiod, phenology and productivity of Chinook, Columbus, Cascade and Yakima Gold hop cultivars grown in the municipalities of Lages and São Joaquim in Santa Catarina state, southern Brazil. The phenological stages evaluated were: beginning of sprouting, emission of lateral branches, beginning of flowering, formation of cones and beginning of harvest in the 2018/2019 production cycle. Photoperiod and solar brightness were calculated with data obtained from the Environmental Resources and Hydrometeorology Information Center of Santa Catarina State, in Lages and São Joaquim. The observed results demonstrate hops develops at latitude 27º South, there was a difference in behavior in the phenological cycle of the cultivars, characterizing Yakima Gold as early, with 143 days and Columbus with 191 days, late. Since the first agricultural harvest, there is the production of cones. With 5.87 hours per day solar brightness average, in Lages, 3,300 kg of fresh hops were produced per hectare. In São Joaquim, with a 5.53 hour per day solar brightness average, 6,000 kg of fresh hops were produced per hectare.
Keywords: Humulus lupulus L.; phenology; photoperiod; solar brightness